Parasitismo em Cnemidophorus ocellifer (Squamata:Teiidae) de quatro ecossistemas do nordeste brasileiro - Eloi, Felipe Jardelino (2013)
Parasite is an organism that lives inside (endo) or in surface (ectoparasites) from another organism, the host, feeding, showing some degree of adaptation and causing some damage to it. In Brazil one of the most commonly found lizard is the Cnemidophorus ocellifer, active forager, with wide national distribution except Amazon, and diurnal heliotherms, which mainly inhabits open areas. Therefore, this study aims to characterize the patterns of infestation by parasites in populations of C. ocellifer in four ecoregions of northeastern Brazil, the abundance, composition, diversity and body distribution. We examined 399 specimens of C. ocellifer. Eutrombicula alfreddugesi was the only ectoparasite species found in all populations studied. The Sete Cidades population was the most parasitized with 9,819 mites found, and the population of Barra Cunhaú was less parasitized, with only 445 individuals and 66 mites free from ectoparasites. We found six types of endoparasites: Platyhelminths Cestoda (n=49) and Nemathelminths Pharyngodon sp. (n=1633) in stomachs and intestines, Nemathelminths Piratuba sp. (n=6), Oswaldofilaria sp. (n=17) and Physaloptera spp. (n=1), only in coelomic cavities in Sete Cidades, and Pentastomid Raillietiella mottae (n=5) in the lungs only in Barra do Cunhaú. For ectoparasites males are significantly more infested than females and this is probably linked to the inverse relationship that exists between testosterone levels in the blood and immune system efficiency. The sites of infestation were instrumental in the infestation by ectoparasites in all populations studied, indicating mainly post-inguinal regions as significantly more infested sites in all populations. These results are not only related to the presence of dermal folds in these regions, since there are folds in other parts of the body of these lizards and they showed no such significant results. The infestation was also partially influenced by the environment, but it may be that this is influenced by secondary factors and not necessarily environmental. Body condition, another fitness parameter, was also partially influenced by parasitic infestation, but not as expected, where most infected individuals have better body condition, refuting the hypothesis (individuals with greater intensity would be less parasitic body condition score). An overview of all these results suggests that the infestation by ectoparasites can be associated with characteristics of fitness and sexual selection, corroborating the Handicap Theory. If not this way, a parasite can present with its host, a neutral relationship (comensal) or even positive, even at low level (mutual). Endoparasites may be acting illegitimate way, without the hosts in no way benefit from this interaction, but can at least present a pattern of species diversity known for other taxa.